NON-NECROTIZING DIFFUSE ANTERIOR SCLERITIS SEBAGAI MANIFESTASI OKULER TERISOLASI DARI LUPUS ERYTHEMATOSUS SISTEMIK: LAPORAN KASUS - Kara Citra Kalandra; Rifna Lutfiamida (Majalah Oftalmologi Indonesia, 2023)
Introduction: Systemic lupus erythematosus (SLE) is an autoimmune disorder with heterogeneous clinical manifestation in numerous organ systems, including the eye. Ocular involvements have been reported in up to one-third of patients with SLE, although scleritis is considered a less common manifestation of the disease found in only about 1% of cases Case Report: A 46-year-old female patient presented with a painful right eye for 1 week. She reported having the same symptom last year which resolved without treatment. There was no known history of systemic immune-mediated diseases and no prior ocular trauma. Ophthalmological examination revealed dilatation of deep scleral vessels on the right eye. The patient tested positive for the antinuclear antibody and anti-double-stranded deoxyribonucleic acid tests. She was diagnosed with non-necrotizing diffuse anterior scleritis caused by SLE and was treated with topical prednisolone acetate and systemic methylprednisolone. After 1 week of treatment, the patient showed an improvement in ocular signs and symptoms. Discussion: Scleritis is a rare inflammatory disease usually associated with systemic immune-mediated diseases such as SLE. It can cause significant visual loss and may be life-threatening. We reported a non-necrotizing diffuse anterior subtype of scleritis presented as an isolated manifestation in SLE, which benefited from early diagnosis and treatment of corticosteroids. Conclusion: Scleritis may present as an early or isolated manifestation of systemic immune-mediated disease. Therefore, a comprehensive examination is of the essence to exclude multisystem disease and treat the underlying cause even when there is no systemic manifestation.